Efektivitas Pendidikan Pesantren Salafiyah di Tengah Modernisasi di Pondok Pesantren Assanusi Babakan Ciwaringin, Cirebon - Faisal, Akhmad; Ahmad, Nurwadjah; Suhartini, Andewi (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2022)
This study aims to try to analyze the education system of the Salafiyah Assanusi Islamic boarding school amid modernization. The method in this study was conducted using a case study qualitative approach. Data was obtained through observation, interviews, and documentation. The subjects of this study were the people of the Assanusi Islamic Boarding School, Babakan Ciwaringin, Cirebon, using the sources of informants: Kyai, Teachers, Administrators, and Santri. The results of this study the researchers found that there was a change in the education system at the Assanusi Islamic boarding school from a traditional education system to a modern education system in the aspects of institutions, buildings, and learning methods in formal schools that refer to the K13 learning curriculum through the Ministry of Education and Culture, but in terms of Religious science learning in Islamic boarding schools is still running using the sorogan, wetonan and bandongan and still preserving the elements of the Salafiyah Islamic boarding school, namely Kyai, santri, yellow books, mosques and huts as dormitories where the students and Kyai live without losing their values. Islamic values by teaching the yellow books as a learning curriculum which is the hallmark of the Salafiyah Islamic Boarding School. These changes are influenced by factors outside the Assanusi Islamic boarding school, which have developed according to the development and needs of the community at this time. So the Assanusi Islamic Boarding School must prepare graduates who are ready to enter the community with Islamic values and general knowledge at this time.